2021
DOI: 10.3390/w13091239
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Future Impact of Climate Change on the Hydrology of the Mangoky River, Madagascar Using ANN and SWAT

Abstract: The assessment of the impacts of climate change on hydrology is important for better water resources management. However, few studies have been conducted in semi-arid Africa, even less in Madagascar. Here we report, climate-induced future hydrological prediction in Mangoky river, Madagascar using an artificial neural network (ANN) and the soil and water assessment tool (SWAT). The current study downscaled two global climate models on the mid-term, noted the 2040s (2041–2050) and long-term, noted 2090s (2091–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Further comparison is needed to determine the more e cient approach to select the methods based on the processing and analysing tasks. More so, more dynamic updates are required by the developers of General Circulation Models (GCMs) to improve climate modeling resulting in high emissions [45].…”
Section: Open Research Directionsmentioning
confidence: 99%
“…Further comparison is needed to determine the more e cient approach to select the methods based on the processing and analysing tasks. More so, more dynamic updates are required by the developers of General Circulation Models (GCMs) to improve climate modeling resulting in high emissions [45].…”
Section: Open Research Directionsmentioning
confidence: 99%
“…The SWAT model is a spatially distributed hydrological model that was designed to assist water resource managers in assessing the impacts of climate change, land use, and management approaches on water resources [34,35]. This model has been widely employed by researchers for watershed modeling and water resource management in watersheds with different climatic and topographic characteristics, owing to its user-friendly interface (ArcSWAT) and flexible data needs [27,36]; it has already been validated for various watershed scales in different climatic situations around the world, and it has worked well even in complex and data-poor watersheds [37]. The SWAT model also has the advantage of allowing the simulation of a variety of physical processes (e.g., hydrological, sediment, and contaminants) in a watershed.…”
Section: Swat Modelmentioning
confidence: 99%
“…During the rainy season (Figure 8c), less significant increases and decreases in precipitation were projected under SSP126 in both periods, which should result in increased runoff. However, a decrease was predicted, which could be associated with a significant increase in ET due to increased maximum and minimum temperatures [27,83]. Temperature effects tend to dominate in the 21st century under the high-emissions scenario, which had a significant impact on reducing runoff despite the predicted increase in precipitation during the rainy season [84,85].…”
Section: Surface Runoff Under Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that neural networks could efficiently forecast future evapotranspiration even with the constraint of having limited climate parameters as inputs, Additionally, they are commented that the accuracy could be significantly improved by addition of a greater number of inputs. Rabezanahary, et al [19] also focused their work on predicting the future precipitation and temperature at Mangoky River, Madagascar. 26 causative variables were chosen with the help of a linear measure (coefficient of correlation) calculated between the predictors and the desired output (Temperature and pressure).…”
Section: Introductionmentioning
confidence: 99%